Assessing soil quality under long-term rice-based cropping system - Chaudhury, J; Mandal, U.K; Sharma, K.L; Ghosh, H; Mandal, B (Communications in soil science and plant analysis, 2005)
Productivity of the rice-based cropping system is low, and it continues to decline in India because of worsening soil-related constraints. Keeping in view the importance of soil quality in rice-based intensive cropping system, the present investigation was undertaken with the objective of identifying several biological, chemical, and physical indicators of soil quality using data collected from a long-term experiment being conducted since 1972 on rice-wheat-jute cropping system in Indo Gangetic alluvial soils of India. The experiment was laid out in a randomized block design with five treatments, under long-term fertilizer experiment [i.e., control (no fertilizer and manure); 100% of the recommended dose of nitrogen (100% N); 100% of the recommended dose of N and phosphorus (100% NP); 100% of the recommended dose of N, P, and potassium (100% NPK); and 100% of the recommended dose of N, P, K, and farm yard manure (100% NPK + FYM]. Soil samples were collected after the harvest of rice during the 2002 experiment and were analyzed for physical, chemical, and biological parameters. On the basis of the long-term yield data, sustainable yield index was calculated. Multivariate statistical techniques were used to determine the smallest set of chemical, physical, and biological indicators that account for at least 95% of the variability in the total data set. The total soil N, available P, dehydrogenase activity, and mean weight diameter of the aggregates were the most important indicators in this case study. A multiple regression was run to evaluate the efficacy of minimum data set (MDS) taking sustainable yield index as goal (r2 = 0.69). Each MDS was transformed into score. The soil quality index (SQI) was calculated by using weighing factors derived from principal component analysis for each scored MDS variable. The highest SQI was found in 100% NPK + FYM treatment followed by 100% NPK, 100% NP, 100% N, and control treatment, respectively. To compare the soil aggradation or degradation, an undisturbed fallow soil was taken as reference, and it has been observed that 100% NPK + FYM and 100% NPK showed positive change in soil quality that is aggradation of soil quality, but the other three treatments, 100% N, 100% NP, and control, showed negative change of soil quality and indicates degradation of the system.